"ONE THOUSAND AND ONE NIGHTS" AND COMPARATIVE INTERPRETATION IN WESTERN LITERARY STUDIES. - Vakhidova Mushtariy Uktamovna (Western European Studies, 2025)
This article is devoted to the comparative interpretation of the work “One Thousand and One Nights”, one of the most famous masterpieces of Eastern literature, in Western literary studies and its influence on literary processes. The rise of Oriental science in the 11th–14th centuries had a significant impact on the European Renaissance, and the stories of “One Thousand and One Nights” entered European culture, especially through translations of Arabic, Persian and Indian literature. Jean Antoine Gallant’s translation into French sharply increased interest in this work throughout Europe. Studies conducted based on the methods of comparative literary studies reveal that the plots and images of “One Thousand and One Nights” had a significant impact on the work of Western writers such as Pedro Alfonso, Juan Manuel, J. Boccaccio, W. Beckford, T. Moore, Andersen, Pushkin and Goethe. The narrative style, symbolic imagery, and colorful plots of the novel inspired the formation of new genres and compositional forms in European literature. The work is valued not only artistically, but also philosophically as a bridge of cultural dialogue between Eastern and Western cultures
Keywords: One Thousand and One Nights; Eastern literature; Western literature